Capital Flow Deflection - Giordani, Paolo E.; Ruta, Michele; Weisfeld, Hans; Zhu, Ling (Elsevier, 2018)
This paper focuses on the coordination problem among countries imposing controls on capital inflows. In a simple model of capital flows and controls, we show that inflow restrictions distort international capital flows to other countries and that, in turn, such capital flow deflection may lead to a policy response. We then test the theory using data on inflow restrictions and gross capital inflows for a large sample of developing countries between 1995 and 2009. Our estimation yields strong evidence that capital controls deflect capital flows to other countries with similar economic characteristics. Notwithstanding these strong cross-border spillover effects, we do not find evidence of a policy response.